FEATURES OF PRINTING PRODUCTION IN MODERN CONDITIONS - K.E. Grishin,; Djabbarova Yulduz Abduvaliyevna, (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
In this article, general trends in the market of book products are discussed, as well as the volume of the publishing market, which depends on the number of publishers and the scale of their activities, effective demand and the number of readers.